Paraquat Behavior in Costa Rican Soils and Residues in Coffee - Constenla Umaña, Manuel Arturo (1990)
The paraquat deactivation capacities of soils, from 20 coffee plantations, generally ranged from 100 to 500 mg of paraquat/kg of soil. Even when paraquat had been applied up to twice per year (1.2 kg ha-1 year) for 20 years, residues were less than 10% of the soils’ deactivation capacities and in the majority of cases were less than 1 %. Residues in coffee berries and beans were at or below the limit of determination of 0.02 mg/kg. This confirmed that strongly adsorbed residues in soil are not absorbed by the crop and there is no translocation of residues into the crop following accidental contamination of bushes during spraying.